MCBS Highlights: Ownership and Average Premiums for Medicare Supplementary Insurance Policies - Chulis, George S. (CENTERS for MEDICARE & MEDICAID SERVICES, 1995)
This article describes private supplementary health insurance holdings and average premiums paid by Medicare enrollees. Data were collected as part of the 1992 Medicare Current Beneficiary Survey (MCBS). Data show the number of persons with insurance and average premiums paid by type of insurance held—individually purchased policies, employer-sponsored policies, or both. Distributions are shown for a variety of demographic, socioeconomic, and health status variables. Primary findings include: Seventy-eight percent of Medicare beneficiaries have private supplementary insurance; 25 percent of those with private insurance hold more than one policy. The average premium paid for private insurance in 1992 was $914.